Driving the life course approach to vaccination through the lens of key global agendas - Stancu, Andra; Khan, Anusheh; Barratt, Jane (Frontiers in Aging, 2023)
Globally, population is ageing at an unprecedented rate and by 2030, which marks the end of the United Nations (UN) Decade of Healthy Ageing, the number of people aged 60 years and older will be 34% higher than today, reaching 1.4 billion. Parallel to population ageing is the increase in prevalence of non-communicable diseases (NCDs) which increase the risk of severe consequence from vaccine preventable diseases. Vaccination is one of the most effective public health interventions of modern times and a key action in fostering healthy ageing throughout the life-course. To promote well-being at all ages, global agendas including the WHO Immunization Agenda 2030, the UN Decade of Healthy Ageing and the WHO Global Report on Ageism outline strategic actions and guidance to help implement policies and programs. Yet, the linkages between healthy ageing, functional ability and adult vaccination are not substantively recognized or integrated as cross-cutting themes, which impacts operationalization into national immunization plans. When aligned and connected strategically, these agendas have potential to substantially contribute to policy change to prioritize life-course immunization and support the preservation of function at all stages of life. This article describes the intersecting goals and visions of these strategic agendas and identifies specific elements of overlap which when connected could strengthen the development of comprehensive and effective national immunization policies.